Образи природного оточення як стани екзистенції у поезії Олени Теліги та Зельми Меербаум-Айзінгер - Самолюк, О. (Літературознавчі обрії. Праці молодих учених, 2010)
The attention in the article is concentrated on the intertextual dialogue between the poetry by Olena Teliha and Selma Meerbaum-Eisinger. The images-landscapes and their explication are considered in connection with one’s condition of existence reflected in poetic text. Similar words-images are investigated in the works of the above mentioned poets.